2016
DOI: 10.1371/journal.pone.0165985
|View full text |Cite
|
Sign up to set email alerts
|

Soil Salt Distribution and Tomato Response to Saline Water Irrigation under Straw Mulching

Abstract: To investigate better saline water irrigation scheme for tomatoes that scheduling with the compromise among yield (Yt), quality, irrigation water use efficiency (IWUE) and soil salt residual, an experiment with three irrigation quotas and three salinities of irrigation water was conducted under straw mulching in northern China. The irrigation quota levels were 280 mm (W1), 320 mm (W2) and 360 mm (W3), and the salinity levels were 1.0 dS/m (F), 3.0 dS/m (S1) and 5.0 dS/m (S2). Compared to freshwater, saline wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…However, the Japanese cultivars had lower LAI than the Dutch cultivars (Table 1). Moreover, Saito et al (2009) stated that salinity stress starting at first flower anthesis of the first truss reduced the total dry weight with high EC (8.0 dS•m −1 ) under the NFT system and Zhai et al (2016) indicated that LAI decreased as the salinity level increased with EC values of 1.0, 3.0, and 5.0 dS•m −1 under hydroponic and soil culture. In this experiment, salinity treatment was started at the fourth flower anthesis of the first truss with an EC of 6.0 dS•m −1 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the Japanese cultivars had lower LAI than the Dutch cultivars (Table 1). Moreover, Saito et al (2009) stated that salinity stress starting at first flower anthesis of the first truss reduced the total dry weight with high EC (8.0 dS•m −1 ) under the NFT system and Zhai et al (2016) indicated that LAI decreased as the salinity level increased with EC values of 1.0, 3.0, and 5.0 dS•m −1 under hydroponic and soil culture. In this experiment, salinity treatment was started at the fourth flower anthesis of the first truss with an EC of 6.0 dS•m −1 .…”
Section: Discussionmentioning
confidence: 99%
“…5G , 5H ) when strong evaporation likely induced soil salinization ( Marcos et al, 2018 ; Yang et al, 2011 ), and mulched drip irrigation washed the soil salt out from the root zone (0–60 cm depth). However, due to the small rate of discharge of mulched drip irrigation, soil salt was difficult to flush into the groundwater (8 m depth) and accumulated beneath the root zone ( Zhai, Yang & Wu, 2016 ; Wang, Fan & Guo, 2019 ). This finding was consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the long-term abandonment of farmland, the nutrient content of heavily saline-sodic soils is poor, which significantly restricts land reclamation for agricultural utilization [29]. For example, saline-sodic soils are rich in exchangeable calcium ions and calcium carbonate [30], thus, when calcium ions and phosphate ions form insoluble calcium phosphate precipitates, the soil has a strong fixation effect on phosphorus. Although the total phosphorus content in the soil is very high, there is a severe lack of available phosphorus [31].…”
Section: Fermenting Straw Return Proved Beneficial For Reducing the E...mentioning
confidence: 99%